Design and Experiment of a Heat Pump Air-conditioning System for Electric Vehicles - Li Li; Wei Mingshan; Peng Fazhan; Zhang Hong (Zhileng xuebao, 2013)
A cooling and heating dual-mode heat pump air-conditioning system has been developed for pure electric vehicles and a test bench has been built. The performances of heating mode at different circumstances temperature was tested and analyzed. The results showed that the heat pump air-conditioning system was feasible and could meet the temperature requirements of the vehicle cabin in a short time. The performance of the heat pump air conditioning system was affected by the ambient temperature. When the ambient temperature was lower, the pressure in the pipeline and the discharge temperature of the compressor was lower, so the heating capacity per unit time is less.